(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The article proposes general theoretical provisions of the policy of proportional territorial development of tourism as a separate direction of regional policy (objects, subjects, goals, methodology, justification of the necessity, etc.). The aforementioned provisions were localized on the example of the Republic of Armenia, substantiating the urgent need for a state policy of proportional territorial development of tourism in Armenia․